ATTITUDE OF ISLAMIC STUDIES STUDENTS TOWARDS LEARNING ARABIC LANGUAGE: SECONDARY SCHOOLS IN ASA LOCAL GOVERNMENT - Solahudeen, Owoyale-Abdulganiy Ibrahim; Nurudeen, Babatunde; Shehu, Aliyu; Yahya, Isiaq Oluwatosin (Universitas Labuhanbatu, 2025)
Purpose-The study examined the Attitude of Islamic studies students toward learning the Arabic language in Asa Local Government, Kwara State, Nigeria.Methodology-The study involved senior secondary school students of Islamic studies who offered Arabic Language courses in schools. To do justice to this paper, the researcher used relevant materials such as textbooks, journals from the Internet, and other relevant materials in the course of this study.Findings-The study's findings revealed that most Islamic studies students have positive Attitudes toward the Arabic language and that Islamic studies students' competence in learning the Arabic language is relatively poor. It is concluded that teachers and students of the Arabic Language should be given adequate support to enhance effective teaching and learning of the Arabic Language. Recommendations include improving teacher training, curriculum design, and a more supportive environment for Arabic language education.Significance-This paper underscores the need for collaborative efforts among stakeholders to enhance students' motivation and performance in Arabic learning, ultimately bridging the gap between Islamic Studies and Arabic language acquisition. Keywords : Attitude; Arabic Language; Islamic Studies; Learning.